The Effect Of Competence And Self-Efficacy On Employee Performance With Work Discipline As A Moderating Variable In Chocolate SMEs In Badung Regency - Ni Nyoman Ari Novarini; I Ketut Setia Sapta; Liana Ayu Ananda Putri (International Journal of Applied Science and Sustainable Development (IJASSD), 2026)
The present study investigates the influence of competence and self-efficacy on employee performance. Work discipline is examined as a moderating variable in a chocolate-based small and medium-sized enterprise in Badung Regency, Indonesia. The research employed a quantitative causal approach, involving all 58 employees of the Junglegold Chocolate Factory. The selection of these employees was conducted through a saturated sampling technique. Primary data were obtained using a structured questionnaire measured on a five-point Likert scale and analyzed through Partial Least Squares Structural Equation Modeling using SmartPLS 25. The findings indicate that competence exerts a positive and significant influence on employee performance. Self-efficacy has been demonstrated to have a significant impact on employee performance. Furthermore, the impact of work discipline on the relationship between competence and employee performance, as well as the relationship between self-efficacy and employee performance, is found to be significant. The findings suggest that employee competence and psychological confidence, when supported by disciplined work behaviors such as punctuality, responsibility, adherence to rules, and consistent task completion, are more effective in improving performance. This study makes a significant contribution to the field of human resource management by underscoring the strategic importance of work discipline in enhancing employee performance within the context of SMEs.